The safety of ramucirumab for the treatment of colorectal cancer. Issue 9 (2nd September 2018) - Noguerido, Alba; Mulet-Margalef, Núria; Matos, Ignacio; Ros, Javier; Argilés, Guillem; Élez, Elena; Tabernero, Josep
ABSTRACT: Introduction : Ramucirumab, a human monoclonal antibody against vascular endothelial growth factor receptor 2 (VEGFR-2), is an antiangiogenic therapy that has been approved in combination with FOLFIRI in second-line treatment of metastatic colorectal cancer (mCRC), after progression on or after therapy with bevacizumab, oxaliplatin, and a fluoropyrimidine. A thorough review of the safety of ramucirumab in this setting and in the context of other antiangiogenic agents is merited. Areas covered : We provide an overview of activity and summarize in detail the overall safety and tolerability profile of ramucirumab in mCRC patients on the basis of a literature review of all published clinical trials in this setting, including both single-agent and combination studies. A focus on adverse events of interest and specific populations is included, as well as a critical comparison with other antiangiogenic therapies. Expert opinion : As an effective agent in pretreated mCRC patients, the toxicity profile of ramucirumab is similar to those of other angiogenesis inhibitors used in the second-line mCRC setting. The next challenge will be to find biomarkers of response and toxicity to antiangiogenic therapies in order to more effectively implement personalized medicine in these patients.